ChemInform Abstract: Highly Efficient and Chemoselective α‐Iodination of Acrylate Esters Through Morita—Baylis—Hillman‐Type Chemistry. Issue 27 (13th June 2013) - Pace, Vittorio; Vilkauskaite, Gyte; Sackus, Algirdas; Holzer, Wolfgang
Abstract The reaction works also well with multifunctionalized acrylate esters, providing excellent chemoselectivity.